Contribution of Cytogenetics to the Debate on the Paraphyly of Pachycondyla spp. (Hymenoptera, Formicidae, Ponerinae) - Cléa dos Santos Ferreira Mariano; Silvia das Graças Pompolo; Janisete Gomes Silva; Jacques Hubert Charles Delabie (Psyche: A Journal of Entomology)
We present evidence of the paraphyly of the ant genus Pachycondyla resulting from our cytogenetic studies on 29 populations in 18 species from Brazil and French Guyana. It is likely that karyotypes with a large number of chromosomes and comprising mostly small acrocentric chromosomes in species within the Pachycondyla stricto sensu group resulted from a succession of centric fission events. On the other hand, karyotypes with a small chromosome number comprising mostly metacentric chromosomes are also interpreted as little derived and tend to undergo centric fission. The karyotypes of the group Neoponera are more heterogeneous and probably undergo successive cycles of rearrangements tending to increase the chromosome number by centric fission. The apicalis and verenae complexes form two probable sister groups that evolved independently due to centric fissions (verenae) and pericentric inversions (apicalis). Our results reveal the karyotype diversity in the genus and reinforce the hypothesis on the paraphyly of Pachycondyla.